Liver stage antigen 3 Plasmodium falciparum peptides specifically interacting with HepG2 cells (2004)
Binding assays were carried out with 20 amino acid long peptides covering the complete 200-kDa Liver stage antigen (LSA) 3 protein sequence to identify its HepG2 cell binding regions. Seventeen HepG2 cell high-activity binding peptides (HABPs) were identified in the LSA-3 protein. Seven HABPs were found in the nonrepeat (NRA) region A; five of these formed a 100 amino acid long HepG2 cell binding region located between residues 21Ile and 120Thr. Six HABPs were found in the R2 region and another four in the NRB2 region. LSA-3 protein HABPS bound saturably to HepG2 cells having nanomolar affinity constants and bound specifically to 31, 44, and 70 kDa HepG2 cell membrane proteins. Some of them were located in antigenic and immunogenic LSA-3 protein regions. Immunofluorescence and immunoblotting assays using goat sera immunized with LSA-3 protein peptides recognized P. falciparum (FCB-2 strain) erythrocyte stage proteins (58, 68, 72, 81, 86, 160, and 175 kDa). This reactivity was due mainly to the VEESVAEN motif present in some erythrocyte stage proteins. However, our results suggest that antibodies against LSA-3 regions had a crossed reaction with another 86-kDa protein, and that this crossed reaction was due to a motif present in the NRA region.